Lost in Paris [videorecording (DVD)] - Abel, Dominique, 1957-; Abel, Dominique, 1957-; Gordon, Fiona, 1957-; Gordon, Fiona, 1957-; Riva, Emmanuèle (Oscilloscope Laboratories, 2017)
Filmed in Dominique Abel and Fiona Gordon's signature whimsical style, and stars the filmmakers as a small-town Canadian librarian and a strangely seductive, oddly egotistical French vagabond. When Fiona's orderly life is disrupted by a letter of distress from her elderly Aunt Martha who is living in Paris, Fiona hops on the first plane she can and arrives only to discover that Martha has disappeared. In an avalanche of spectacular disasters, she encounters Dom, the affable, but annoying tramp won't leave her alone.